PENINGKATAN KEMAMPUAN KADER POSYANDU DALAM PEMANTAUAN TUMBUH KEMBANG BAYI BALITA PADA MASA NEW NORMAL DI DESA PANDAU JAYA KABUPATEN KAMPAR - ELLY SUSILAWATI; YANTI, YANTI; FINDY HINDRATNI (KRIDA CENDEKIA, 2021)
The purpose of this community service activity is to conduct training for Posyandu cadres to increase their knowledge and ability to monitor the growth and development of infants under five in the new normal period in Pandau Jaya village, Siak Hulu district, Kampar district in 2021. The method of community service activities is carried out by conducting socialization community service activities for village officials, posyandu cadres and the medical team of the Siak Hulu Health Center at the Pandau Jaya village office, providing material for Posyandu cadres in the Village Office Hall (Basic concepts for Toddler Infant Development, How to assess growth in infants and toddlers), (how to assessing the development of infants and toddlers), (Implementation of services at Posyandu using health protocols during the new normal period), (Demonstrations of assessing the growth and development of infants under five, as well as handling that can be carried out by cadres if they find signs of abnormal symptoms that occur in children. ), the practice of assessing the growth and development of infants under five by cadres at the Posyandu, and evaluating activities. The result of this community service activity is that socialization activities and provision of growth assessment materials for infants and toddlers have been carried out, followed by the practice of assessing the growth and development of infants under five by cadres at Posyandu, and evaluating activities. Based on the results of monitoring and evaluation, it was found that there was an increase in participants’ knowledge with an average Pre Test score of 62 to 80 Post-Test average scores. It is recommended to cadres to routinely monitor growth and development of infants and toddlers who come to the Posyandu at the time of weighing and not only weighing but also being able to do growth monitoring analysis plus an assessment of the development of infants and toddlers in order to detect early on in infants and toddlers who the possibility of experiencing stunting so that referrals and appropriate actions can be taken to overcome the problems found. And the Siak Hulu Health Center can provide guidance and evaluation so that cadres become more skilled in monitoring the growth and development of infants and toddlers in Pandau Jaya Village.